A composite decoloring agent for industrial wastewater and a preparation method thereof

CN122608139BActive Publication Date: 2026-10-20JIANGSU JIANLIN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611089156.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20
Estimated Expiration
2046-07-22

AI Technical Summary

Technical Problem

[0003]印染废水的治理除了通过混凝法、吸附法等去除水体中有机污染物,降低COD,还有一大难题--未反应的染料、颜料带有隆重的色泽

Benefits of technology

[0014]与现有技术相比,本发明的有益效果是:本发明以凹凸棒土为载体,通过对其进行氨基化和羧基化改性后,使其能够作为MOF的生长位点,引导铁基MOF晶体在其表面原位生长,形成均匀牢固的MOF壳层,界面结合强度高,结构稳定性好;由此形成吸附-富集-催化降解的多效脱色剂。而后又通过KH570作为桥接剂,在凹凸棒土表面继续原位生长聚丙烯酰胺和甲基丙烯酰氧乙基三甲基氯化铵,构建阳离子聚合物刷,进一步通过静电相互作用选择性捕获带负电的阴离子染料,提高脱色性能。聚合硫酸铝和活性炭辅助提供絮凝和吸附功能,加快脱色剂网捕染料分子的速率,有效提高对染料分子的处理效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present case relates to a kind of composite decoloring agent for industrial wastewater and its preparation method, first to attapulgite is activated, then amino and carboxylation are carried out in turn;Then add to the iron chloride solution, with organic ligand, MOF crystal is in situ grown on its surface, finally by KH570 and acrylamide monomer graft copolymerization, the composite material obtained and polyaluminum sulfate and activated carbon are compounded, and the composite decoloring agent is obtained.The present application uses attapulgite as carrier, iron-based MOF crystal is in situ grown on its surface, forms uniform and firm MOF shell layer, interface bonding strength is high, and structure stability is good;From this, the multi-effect decoloring agent of adsorption-enrichment-catalytic degradation is formed;Surface constructs cationic polymer brush, further selectively captures negative anionic dye through electrostatic interaction, improves decoloring performance;Polyaluminum sulfate and activated carbon auxiliary provide flocculation and adsorption function, effectively improve the processing efficiency of dye molecule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment agent preparation technology, specifically to a composite decolorizing agent for industrial wastewater and its preparation method. Background Technology

[0002] Industrial wastewater includes production wastewater, industrial sewage, and cooling water. It refers to the wastewater and waste liquid generated during industrial production processes, containing industrial raw materials, intermediate products, by-products, and pollutants lost with the water. Industrial wastewater is diverse and complex in composition, including metallurgical wastewater, papermaking wastewater, coking gas wastewater, metal pickling wastewater, chemical fertilizer wastewater, textile printing and dyeing wastewater, dye wastewater, leather tanning wastewater, pesticide wastewater, and power plant wastewater. Statistics show that the wastewater discharged by my country's printing and dyeing industry accounts for 80% of the total wastewater discharge from the entire textile industry, making it one of the largest and most polluting wastewater discharges. Printing and dyeing wastewater is the wastewater discharged from printing and dyeing factories, wool dyeing and finishing factories, and silk factories that primarily process cotton, linen, chemical fibers and their blended products, and silk. This wastewater contains dyes, sizing agents, auxiliaries, oils, acids and alkalis, fiber impurities, sand, inorganic salts, etc., and is characterized by large volume, high organic pollutant content, high alkalinity, and significant water quality fluctuations.

[0003] In addition to removing organic pollutants and reducing COD through methods such as coagulation and adsorption, another major challenge in treating dyeing and printing wastewater is the presence of unreacted dyes and pigments with strong colors. Therefore, decolorization must also be considered in the treatment of dyeing and printing wastewater. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention uses modified attapulgite as a carrier and forms an MOF shell on the surface of the attapulgite through an in-situ growth strategy. KH570 is used as a bridging agent to construct a quaternized polymer brush. Finally, it is compounded with polyaluminum sulfate and activated carbon to prepare a composite decolorizing agent.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a composite decolorizing agent for industrial wastewater includes the following steps: 1) Attapulgite is activated and pretreated under acidic conditions, then dispersed in an organic solvent, and an aminosilane coupling agent is added and refluxed to obtain aminated attapulgite. 2) Aminated attapulgite is dispersed in an anhydrous solvent containing acid anhydride, and undergoes a ring-opening acylation reaction under the catalysis of triethylamine to obtain carboxylated attapulgite. 3) Carboxylated attapulgite was ultrasonically dispersed in ferric chloride solution, mixed evenly, and then DMF solution of organic ligand was added. The mixture was ultrasonically dispersed for half an hour, and then hydrothermal reaction was carried out to obtain iron-based MOF-attapulgite composite material. 4) The iron-based MOF-attapulgite composite material was redispersed in an organic solvent, KH570 was added and the reaction was refluxed overnight. After filtration, it was redispersed in an ethanol aqueous solution, acrylamide and methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, ammonium persulfate was added as an initiator to carry out a free radical polymerization reaction to obtain the quaternized iron-based MOF-attapulgite composite material. 5) After adding polyaluminum sulfate and activated carbon to a ball mill and grinding them together, the mixture is dispersed in ethanol and the quaternary ammonium iron-based MOF-attapulgite composite material is added. The mixture is stirred at 50°C for 30 minutes, filtered, dried, pulverized and sieved to obtain the composite decolorizing agent.

[0006] Furthermore, the specific process of step 1) is as follows: After pulverizing the attapulgite, pass it through a 100-200 mesh sieve, wash it with water to remove impurities, then soak it in a 1M hydrochloric acid solution for activation. Stir at room temperature for 1-3 hours, filter, wash with water until neutral, dry, and pulverize. Disperse the activated attapulgite in toluene using ultrasound, then add an aminosilane coupling agent, reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0007] Further, the aminosilane coupling agent is selected from one of aminopropyltrimethoxysilane coupling agent, aminopropyltriethoxysilane coupling agent, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane; the mass ratio of the aminosilane coupling agent to attapulgite is 1~1.5:1. Furthermore, the specific process of step 2) is as follows: Aminated attapulgite was dispersed in anhydrous DMF, acid anhydride and triethylamine were added, nitrogen gas was introduced, the reaction temperature was controlled at 40℃, and the reaction was stirred for 8-12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol, and dried under vacuum to obtain carboxylated attapulgite.

[0008] Further, the acid anhydride is succinic anhydride or glutaric anhydride; the mass ratio of aminated attapulgite, acid anhydride and triethylamine is 0.5~1:1:0.1~0.3.

[0009] Further, in step 3), the ferric chloride solution is a 0.02 mol / L FeCl3·6H2O aqueous solution, and the mass-to-volume ratio of carboxylated attapulgite in the ferric chloride solution is 1:50~200.

[0010] Furthermore, the organic ligand is selected from one of pyromellitic acid, 2-aminoterephthalic acid, isophthalic acid, and terephthalic acid, and the amount of the organic ligand is 0.8 to 1.5 times the molar amount of iron in the ferric chloride solution.

[0011] Further, in step 4), the mass ratio of iron-based MOF-attapulgite composite material, KH570, acrylamide and methacryloyloxyethyltrimethylammonium chloride is 1:0.05~0.2:0.5~2:0.3~1.5.

[0012] Furthermore, in step 5), the mass ratio of polyaluminum sulfate, activated carbon balls, and quaternary iron-based MOF-attapulgite composite material is 1~3:0.5~2:1.

[0013] The second objective of this invention is to provide a composite decolorizing agent for industrial wastewater prepared by the method described above.

[0014] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention uses attapulgite as a carrier, and after amination and carboxylation modification, it can serve as a growth site for MOFs, guiding the in-situ growth of iron-based MOF crystals on its surface to form a uniform and robust MOF shell with high interfacial bonding strength and good structural stability; thus forming a multi-effect decolorizing agent for adsorption, enrichment, and catalytic degradation. Subsequently, using KH570 as a bridging agent, polyacrylamide and methacryloyloxyethyltrimethylammonium chloride are further grown in situ on the attapulgite surface to construct a cationic polymer brush, which further selectively captures negatively charged anionic dyes through electrostatic interactions, improving decolorization performance. Polyaluminum sulfate and activated carbon assist in providing flocculation and adsorption functions, accelerating the rate at which the decolorizing agent captures dye molecules, effectively improving the processing efficiency of dye molecules. Detailed Implementation

[0015] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0017] Example 1: A composite decolorizing agent for industrial wastewater 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir at room temperature for 3 h, filter, wash with water until neutral, dry and crush; ultrasonically disperse the activated attapulgite in toluene, then add 12 g of aminopropyltriethoxysilane coupling agent (KH550), reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0018] 2) Disperse 8g of aminated attapulgite in 100mL of anhydrous DMF, add 10g of succinic anhydride and 2g of triethylamine, purge with nitrogen, control the reaction temperature at 40℃, stir for 8h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0019] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 5 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 2 g of trimesic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0020] 4) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of anhydrous toluene, 0.5g of KH570 was added and the mixture was refluxed overnight. After filtration, it was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 2.5g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled through for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and the reaction was carried out for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 5) Add 2g of polyaluminum sulfate and 1g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternary ammonium iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0021] Example 2: A composite decolorizing agent for industrial wastewater 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir it at room temperature for 3 h, filter it, wash it with water until neutral, dry it, and crush it; ultrasonically disperse the activated attapulgite in toluene, then add 13 g of aminopropyltrimethoxysilane coupling agent, reflux it overnight, cool it to room temperature, filter it, wash it with anhydrous ethanol, and vacuum dry it to obtain aminated attapulgite.

[0022] 2) Disperse 8g of aminated attapulgite in 100mL of anhydrous DMF, add 10g of glutaric anhydride and 2g of triethylamine, purge with nitrogen, control the reaction temperature at 40℃, stir for 8h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0023] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 5 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 1.8 g of 2-aminoterephthalic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0024] 4) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of anhydrous toluene, 0.5g of KH570 was added and the mixture was refluxed overnight. After filtration, it was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 2.5g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled through for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and the reaction was carried out for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 5) Add 2.2 g of polyaluminum sulfate and 0.8 g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1 g of quaternary iron-based MOF-attapulgite composite material, stir at 50°C for 30 min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0025] Example 3: A composite decolorizing agent for industrial wastewater 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir at room temperature for 3 h, filter, wash with water until neutral, dry and crush; ultrasonically disperse the activated attapulgite in toluene, then add 15 g of aminopropyltriethoxysilane coupling agent (KH550), reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0026] 2) Disperse 10 g of aminated attapulgite in 100 mL of anhydrous DMF, add 10 g of succinic anhydride and 2 g of triethylamine, purge with nitrogen, control the reaction temperature at 40 °C, stir for 8 h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0027] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 8 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 2 g of trimesic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0028] 4) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of anhydrous toluene, 0.5g of KH570 was added and the mixture was refluxed overnight. After filtration, it was redispersed in 100mL of ethanol aqueous solution, 6g of acrylamide and 3g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, 0.09g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and reacted for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 5) Add 2g of polyaluminum sulfate and 1g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternary ammonium iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0029] Example 4: A composite decolorizing agent for industrial wastewater 1) After crushing 10 g of attapulgite, pass it through a 100-200 mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir at room temperature for 3 h, filter, wash with water until neutral, dry and crush; ultrasonically disperse the activated attapulgite in toluene, then add 12 g of γ-aminopropylmethyldiethoxysilane, reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0030] 2) Disperse 8g of aminated attapulgite in 100mL of anhydrous DMF, add 10g of succinic anhydride and 2g of triethylamine, purge with nitrogen, control the reaction temperature at 40℃, stir for 8h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0031] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 5 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 1.7 g of terephthalic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0032] 4) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of anhydrous toluene, 0.5g of KH570 was added and the mixture was refluxed overnight. After filtration, it was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 3g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and reacted for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 5) Add 1.8g of polyaluminum sulfate and 1.2g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternary ammonium iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0033] Example 5: A composite decolorizing agent for industrial wastewater 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir at room temperature for 3 h, filter, wash with water until neutral, dry and crush; ultrasonically disperse the activated attapulgite in toluene, then add 12 g of aminopropyltriethoxysilane coupling agent (KH550), reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0034] 2) Disperse 8g of aminated attapulgite in 100mL of anhydrous DMF, add 10g of succinic anhydride and 2g of triethylamine, purge with nitrogen, control the reaction temperature at 40℃, stir for 8h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0035] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 3 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 1.7 g isophthalic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0036] 4) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of anhydrous toluene, 0.5g of KH570 was added and the mixture was refluxed overnight. After filtration, it was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 2.5g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled through for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and the reaction was carried out for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 5) Add 3g of polyaluminum sulfate and 1.5g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternary ammonium iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0037] Comparative Example 1: 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir it at room temperature for 3 h, filter it, wash it with water until neutral, dry it, and crush it; ultrasonically disperse the activated attapulgite in toluene, then add 12 g of KH570, reflux it overnight, cool it to room temperature, filter it, wash it with anhydrous ethanol, and vacuum dry it to obtain modified attapulgite.

[0038] 2) 5g of modified attapulgite was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 2.5g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and reacted for 6 h to obtain quaternized attapulgite composite material. 3) Add 2g of polyaluminum sulfate and 1g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternized attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0039] Comparative Example 2: 1) After crushing 10 g of attapulgite, pass it through a 200-mesh sieve, wash it with water to remove impurities, then soak it in 100 mL of 1 M hydrochloric acid solution for activation, stir at room temperature for 3 h, filter, wash with water until neutral, dry and crush; ultrasonically disperse the activated attapulgite in toluene, then add 12 g of aminopropyltriethoxysilane coupling agent (KH550), reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

[0040] 2) Disperse 8g of aminated attapulgite in 100mL of anhydrous DMF, add 10g of succinic anhydride and 2g of triethylamine, purge with nitrogen, control the reaction temperature at 40℃, stir for 8h, after the reaction is complete, cool to room temperature, filter, wash with anhydrous ethanol in sequence, and dry under vacuum to obtain carboxylated attapulgite.

[0041] 3) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 5 g of carboxylated attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 2 g of trimesic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0042] 4) Add 2g of polyaluminum sulfate and 1g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0043] Comparative Example 3: 1) Crush 10 g of attapulgite clay, pass it through a 200-mesh sieve, wash it with water to remove impurities, dry it, and then crush it again; 2) Prepare 500 mL of 0.02 mol / L FeCl3·6H2O aqueous solution, ultrasonically disperse 5 g of attapulgite in the above ferric chloride solution, mix evenly, add 50 mL of DMF solution containing 2 g of trimesic acid, ultrasonically disperse for half an hour, then hydrothermally react at 120℃ for 12 h, cool to room temperature, centrifuge, wash with water and dry to obtain iron-based MOF-attapulgite composite material.

[0044] 3) 5g of iron-based MOF-attapulgite composite material was redispersed in 100mL of ethanol aqueous solution, 5g of acrylamide and 2.5g of methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, 0.075g of initiator ammonium persulfate was added. The temperature was raised to 70 ℃ and reacted for 6 h to obtain quaternized iron-based MOF-attapulgite composite material. 4) Add 2g of polyaluminum sulfate and 1g of activated carbon to a ball mill, grind and mix them, disperse the mixture in ethanol, add 1g of quaternary ammonium iron-based MOF-attapulgite composite material, stir at 50℃ for 30min, filter, dry, grind and sieve to obtain the composite decolorizing agent.

[0045] Performance testing: Using Reactive Brilliant Red X-3B as the research object, a simulated dyeing and printing wastewater with a concentration of 100 mg / L was prepared.

[0046] 200 mL of simulated dyeing and printing wastewater was poured into each of the eight beakers. Then, 20 mg of the decolorizing agent from Examples 1-5 and Comparative Examples 1-3 was added to each beaker. 0.2 mL of 30% H2O was added and the mixture was shaken for 30 min. After standing, samples were taken to test the decolorization rate. After the test, the samples were centrifuged, thoroughly washed with ethanol and deionized water, dried, and then re-added to new simulated dyeing and printing wastewater. The steps were repeated five times to obtain the decolorization rate of the fifth test. The retention rate compared to the first decolorization rate was calculated and recorded in Table 1.

[0047] Table 1 Table 1 shows that the composite decolorizing agents of Examples 1-5 achieved a decolorization rate of over 98% for Reactive Brilliant Red within 30 minutes, and exhibited good stability during repeated adsorption-decolorization-separation-regeneration processes. The decolorization rate after the fifth iteration was consistently above 90%, with a retention rate of 90%. This is mainly attributed to the carboxyl groups on the attapulgite surface guiding the in-situ growth of the iron-based MOF to form a robust shell structure with high interfacial bonding strength. The KH570-bridged quaternized polymer brush is anchored to the composite material surface through chemical bonds, resulting in good structural stability. The Fenton-like catalytic degradation of the MOF shell enables in-situ mineralization of dye molecules, mitigating the adverse effects of adsorption saturation on reusability. Comparative Examples 1 and 2 showed a significant decrease in decolorization rate. In contrast, the catalytic degradation of the in-situ grown iron-based MOF is the key factor in improving decolorization efficiency. The hydroxyl radicals (·OH) generated by the MOF shell through Fenton-like catalysis can degrade the adsorbed dye molecules into small colorless molecules, thereby achieving efficient decolorization. The electrostatic adsorption of the cationic polymer brush plays an auxiliary role in enhancing the performance. Comparative Example 3 had the lowest retention rate because the attapulgite was not modified during the preparation process, it was physically blended with MOF, and the cationic polymer brush was not grafted onto its surface and could not play a protective role, resulting in the worst material stability.

[0048] The composite decolorizing agent prepared in Example 1 was used to treat 100 mg / L Acid Blue BGA anionic dye, Neutral Red dye, and Basic Methylene Blue cationic dye. The decolorization rates are recorded in Table 2.

[0049] Table 2 As shown in Table 2, the composite decolorizing agent of the present invention not only has an excellent decolorizing effect on acidic anionic dyes, but also exhibits excellent decolorizing effects on neutral and basic dyes.

[0050] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.

Claims

1. A method for preparing a composite decolorizing agent for industrial wastewater, characterized in that, Includes the following steps: 1) Attapulgite is activated and pretreated under acidic conditions, then dispersed in an organic solvent, and an aminosilane coupling agent is added and refluxed to obtain aminated attapulgite. 2) Aminated attapulgite is dispersed in an anhydrous solvent containing acid anhydride, and undergoes a ring-opening acylation reaction under the catalysis of triethylamine to obtain carboxylated attapulgite. 3) Carboxylated attapulgite was ultrasonically dispersed in ferric chloride solution, mixed evenly, and then DMF solution of organic ligand was added. The mixture was ultrasonically dispersed for half an hour, and then hydrothermal reaction was carried out to obtain iron-based MOF-attapulgite composite material. 4) The iron-based MOF-attapulgite composite material was redispersed in an organic solvent, KH570 was added and the reaction was refluxed overnight. After filtration, it was redispersed in an ethanol aqueous solution, acrylamide and methacryloyloxyethyltrimethylammonium chloride were added, nitrogen gas was bubbled for 30 min, and under nitrogen protection, ammonium persulfate was added as an initiator to carry out a free radical polymerization reaction to obtain the quaternized iron-based MOF-attapulgite composite material. 5) After adding polyaluminum sulfate and activated carbon to a ball mill and grinding them together, the mixture is dispersed in ethanol and the quaternary ammonium iron-based MOF-attapulgite composite material is added. The mixture is stirred at 50°C for 30 minutes, filtered, dried, pulverized and sieved to obtain the composite decolorizing agent.

2. The preparation method of the composite decolorizing agent for industrial wastewater as described in claim 1, characterized in that, The specific process of step 1) is as follows: After pulverizing the attapulgite, pass it through a 100-200 mesh sieve, wash it with water to remove impurities, then soak it in a 1M hydrochloric acid solution for activation. Stir at room temperature for 1-3 hours, filter, wash with water until neutral, dry, and pulverize. Disperse the activated attapulgite in toluene using ultrasound, then add an aminosilane coupling agent, reflux overnight, cool to room temperature, filter, wash with anhydrous ethanol, and vacuum dry to obtain aminated attapulgite.

3. The preparation method of the composite decolorizing agent for industrial wastewater as described in claim 1, characterized in that, The aminosilane coupling agent is selected from one of aminopropyltrimethoxysilane coupling agent, aminopropyltriethoxysilane coupling agent, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane; the mass ratio of the aminosilane coupling agent to attapulgite is 1~1.5:

1.

4. The preparation method of the composite decolorizing agent for industrial wastewater as described in claim 1, characterized in that, The specific process of step 2) is as follows: Aminated attapulgite was dispersed in anhydrous DMF, acid anhydride and triethylamine were added, nitrogen gas was introduced, the reaction temperature was controlled at 40℃, and the reaction was stirred for 8-12 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with anhydrous ethanol, and dried under vacuum to obtain carboxylated attapulgite.

5. The method for preparing the composite decolorizing agent for industrial wastewater as described in claim 1, characterized in that, The acid anhydride is succinic anhydride or glutaric anhydride; the mass ratio of aminated attapulgite, acid anhydride and triethylamine is 0.5~1:1:0.1~0.

3.

6. The method for preparing the composite decolorizing agent for industrial wastewater according to claim 1, characterized in that, In step 3), the ferric chloride solution is a 0.02 mol / L FeCl3·6H2O aqueous solution, and the mass-to-volume ratio of carboxylated attapulgite in the ferric chloride solution is 1:50~200.

7. The method for preparing the composite decolorizing agent for industrial wastewater according to claim 1, characterized in that, The organic ligand is selected from one of pyromellitic acid, 2-aminoterephthalic acid, isophthalic acid, and terephthalic acid, and the amount of organic ligand used is 0.8 to 1.5 times the molar amount of iron in the ferric chloride solution.

8. The method for preparing the composite decolorizing agent for industrial wastewater according to claim 1, characterized in that, In step 4), the mass ratio of iron-based MOF-attapulgite composite material, KH570, acrylamide, and methacryloyloxyethyltrimethylammonium chloride is 1:0.05~0.2:0.5~2:0.3~1.

5.

9. The method for preparing the composite decolorizing agent for industrial wastewater according to claim 1, characterized in that, In step 5), the mass ratio of polyaluminum sulfate, activated carbon balls, and quaternary iron-based MOF-attapulgite composite material is 1~3:0.5~2:

1.

10. A composite decolorizing agent for industrial wastewater prepared by any one of claims 1-9.

Citation Information

Patent Citations

  • High-stability metal organic skeleton hybrid material, preparation method and application thereof

    CN103694260A

  • Ozone removal material and preparation method thereof

    CN109821518A